An assessment of oxidant/antioxidant status in patients with snake envenomation. Issue 1 (22nd December 2012) - Zengin, Suat; Al, Behcet; Yarbil, Pinar; Guzel, Remzi; Orkmez, Mustafa; Yildirim, Cuma; Taysi, Seyithan
Abstract : Objective: The aim of this study is to investigate the antioxidant status (TAS), oxidant status (TOS) and oxidative stress index (OSI) in patients with snake envenomation and to learn more about the pathophysiology of snake envenomation. Method: Between May 2009 and October 2010, 47 patients were admitted to our emergency department with snake bites, and as a control group 20 healthy volunteers were enrolled in this study. Serum, plasma, and erythrocyte components were prepared for all patients on admission and at the control after 1 month. Serum TOS/TAS levels were measured. Results: No correlation was observed among age, gender and the levels of TAS, TOS and OSI. TAS, TOS and OSI levels were higher in snake envenomation patients upon arrival at the emergency department than in the healthy control group. Upon admission, all levels of patients with snake envenomation were higher than the control levels taken after 1 month. Conclusions: Serum TAS, TOS and OSI levels increase in snake envenomation patients. The results obtained in this study indicate that the snake bite was associated with a shift to an oxidative state, and oxidative stress plays an important role in the pathophysiology of snake envenomation.